Examining the Dual Role of Working Women in Kabanjahe and Its Role in Fulfilling Maslow’s Hierarchy of Needs - Malik, Rahman; Hidir, Achmad; Habibi , Abdillah; Paramitha, Nurida Adi; Rahmawati, Amalia (Langgas: Jurnal Studi Pembangunan, 2025)
Needs that are difficult to fulfill due to the lack of a husband's income lead women to enter the public sector, causing a phenomenon called the dual role of women. This research aims to explore how the dual role is experienced by working women in Kabanjahe District, Karo Regency, North Sumatra Province, and its role in fulfilling the hierarchy of needs by Abraham Maslow. The results of this study show that the majority of working women in Kabanjahe District focus on fulfilling physiological needs, which are the most basic needs in Abraham Maslow's hierarchy of needs. The majority of them find it difficult to fulfill other needs because the income earned is focused on fulfilling physiological needs. This phenomenon seems to support and align with Abraham Maslow's theory, that humans will not have time to fulfill other needs if their physiological needs have not been met.